Cardiocerebral channelopathy caused by KCND3 mutation in a child: A case report - Zhang, Yi; Jiang, He; Li, Xiao-mei (Frontiers in Pediatrics, 2022)
Early repolarization syndrome is rare in children. Mutation of genes encoding ion channels could display mixed electrophysiological phenotype of Kv4.3 including both cardiac phenotype (early repolarization syndrome, atrial fibrillation) and cerebral phenotype (epilepsy, intellectual disability). This situation is rare and was named as cardiocerebral channelopathy. Here, we report a case of an 11-year-old-girl with cardiocerebral channelopathy caused by KCND3 mutation, who was successfully treated with oral quinidine, metoprolol and implantable cardioverter-defibrillator. Clinicians should be vigilant on the risk of cardiogenic syncope and sudden cardiac death in a patient with epilepsy, intellectual disability and early repolarization pattern.